Choroidal lesions in patients with AIDS. Issue 10 (October 1990) - Rosenblatt, M. A.; Cunningham, C.; Teich, S.; Friedman, A. H.
Abstract : Seven cases of bilateral, scattered, yellow-white choroidal lesions have been seen in AIDS patients since January 1988. One resulted from presumed extension of cryptococcal meningitis into the optic nerve and choroid. All the remaining six patients had pneumocystis pneumonia at some time during the course of the disease and were receiving aerosolised pentamidine therapy. None died quickly of disseminated Pneumocystis carinii infection, unlike previously reported patients. Mycobacterial infection was also present in five of these six patients. The differential diagnosis of this entity in AIDS patients is discussed.